High‐Performance Organic Solar Cells from Non‐Halogenated Solvents - Wang, Di; Zhou, Guanqing; Li, Yuhao; Yan, Kangrong; Zhan, Lingling; Zhu, Haiming; Lu, Xinhui; Chen, Hongzheng; Li, Chang‐Zhi (Advanced functional materials, 2022)
High‐performance organic solar cells (OSCs) at the current stage are majorly accomplished from the processing of halogenated solvents, such as chloroform, which will be constrained for upscale fabrication due to the adverse health and environmental impacts. Therefore, exploring the high‐performance OSCs from non‐halogenated solvent processing becomes highly necessary, yet largely lagged behind. Herein, it is demonstrated high‐performance OSCs can be obtained from the hot spin processing of different non‐halogenated solvents, and achieve the highest reported efficiency of OSCs from non‐halogenated solvent processing so far. It is revealed that the phase evolution of ternary blends during solution‐to‐solid transition has a correlation to the substrate temperature. With the elevated substrate temperature of hot spin coating, the optimal blend films can be secured in different kinds of non‐halogenated solvents. As result, high‐performance OSCs are obtained with excellent power conversion efficiencies of 18.25% in o‐xylene, 18.20% in p‐xylene, and 18.12% in toluene, respectively. To the author's best knowledge, these results represent the best‐performed OSCs made from non‐halogenated solvents so far. High‐performance organic solar cells (OSCs) are feasibly obtained from the hot spin coating of different kinds of non‐halogenated solvents. It is revealed that the blend phase evolution during solution‐to‐solid transition has a correlation to the substrate temperature. As result, high‐performance OSCs are obtained with power conversion efficiencies of 18.25% in o‐xylene, 18.20% in p‐xylene, and 18.12% in toluene, respectively.